Potential predictive biomarkers in locally advanced rectal cancer treated with preoperative chemo-radiotherapy - Bottarelli, Lorena; de' Angelis, Gian Luigi; Azzoni, Cinzia; Di Mario, Francesco; de' Angelis, Nicola; Leandro, Gioacchino; Fornaroli, Fabiola; Gaiani, Federica; Negri, Francesca (Acta Biomedica Atenei Parmensis, 2018)
Fluorouracil-based preoperative chemoradiotherapy represents a standard option for the treatment of locally advanced rectal cancer. Randomized clinical trials have shown that fluorouracil concomitant to preoperative radiation enhances tumor shrinkage (with 10% to 15% of the patients showing a complete pathological tumor response) compared with preoperative radiation alone. A high response rate is of clinical importance in rectal cancer, since patients who achieve a complete pathological response may experience improved long-term survival. Adding oxaliplatin to fluorouracil-based preoperative chemoradiotherapy has no effect on response of the primary rectal tumor and single-agent fluoropyrimidine remains the standard chemotherapy in this setting. Despite novel biological insights and therapeutic advances, little is known about potential biological markers able to predict pathological tumor response before treatment and to subsequently impact patients’ prognosis. This review focuses on the current available data on main molecular markers and molecular subtypes and the possible upcoming introduction of such analyses in the clinical setting.